Temperature field study of LSAM-50 flexible base asphalt pavement - Bi, Yufeng; Mu, Minghao; Guo, Mengyu; Wu, Wanyu; Ding, Tingting; Qian, Chengduo; Yu, Deshui; Jiang, Yingjun; Su, Hongjian (Frontiers in Materials, 2025)
Recent research has shown that increasing the aggregate particle size and forming a compact, skeleton-dense structure can effectively control reflective cracking and improve rutting resistance of the road, thereby extending the service life of the pavement. To this end, the group developed a super-large particle size LSAM-50 mix (with a maximum nominal particle size ≥50 mm), characterized by low engineering costs, excellent rutting resistance, and the potential to extend the service life of asphalt pavements. The temperature field of LSAM-50 pavement serves as the foundation for evaluating the temperature sensitivity of the material, accurately analyzing the mechanical response of the pavement, and designing a rational pavement structure. Under the combined effects of sunlight, rainfall, wind, and other environmental factors, the internal temperature of asphalt pavement undergoes continuous cyclic changes. During the heat conduction process into the pavement depth, part of the heat is absorbed by the pavement material, resulting in a temperature gradient within the pavement structure. Therefore, the interaction between the natural environment, pavement materials, and other factors is centrally reflected in the spatial and temporal distribution characteristics of the pavement temperature field. Although numerous studies on pavement temperature distribution and prediction models have been conducted both domestically and internationally, significant differences still exist in the temperature distribution of pavements with varying structures and materials, as well as in different regions and terrains.